Clinical-biochemical Observations in Periparturient Dairy Cows with Experimentally Induced Fatty Liver - Theera Rukkwamsuk; Theo Wensing; Henk J. Breukink (Agriculture and Natural Resources, 2007)
In 4 experimental studies, occurrences of health problems during the first 4 weeks of lactation were monitored in 36 control cows and 38 experimental cows that were overfed during the dry period to induce overconditioning at calving and deep negative energy balance and fatty liver postpartum. The experimental cows experienced postparturient problems, including milk fever (37%), acetonemia (8%), abomasal displacement (8%), mastitis (10%), and hoof problems (8%). Acetonemia and abomasal displacement were not observed in the control cows. Milk fever, mastitis, and hoof problems were observed in 3%, 6% and 3% of the control cows, respectively. The experimental cows gained more body weights during the dry period and lost more weights during the first 4 or 5 weeks of lactation than did the control cows. Between 1 and 2 weeks after parturition, the experimental cows had higher concentrations of blood nonesterified fatty acids, blood 3-hydroxybutyrate, and liver triacylglycerols, and had lower concentrations of liver glycogen than did the control cows. Blood glucose and insulin concentrations did not differ between the two groups. When data of the 4 studies were pooled, blood nonesterified fatty acid concentrations were positively correlated with blood 3-hydroxybutyrate and liver triacylglycerol concentrations, and were negatively correlated with liver glycogen concentrations. These results indicated that cows responded to a marked increase in energy requirements in early lactation by increased glycogenolysis in the liver and lipolysis in adipose tissue. In conclusion, overfeeding of cows during the dry period resulted in overcondition at calving. Overconditioning predisposed a cow to develop severe fatty liver postpartum and to experience more postparturient problems. The concentration of blood nonesterified fatty acids postpartum could be used as a routine indicator for the development of fatty liver in dairy cows postpartum.